Suspected geriatric onset of attention-deficit/hyperactivity disorder in a patient with comorbid bipolar disorder - Joshua Woods; Nakisa Kiai; Ranjit Padhy; Rossano Bangasan; Tyler Torrico (BMC Geriatrics, 2024)
Abstract Background An increasing number of adults over 60 years old are presenting with requests for treatment of attention-deficit/hyperactivity disorder (ADHD). However, the prevalence of ADHD in older adults in geriatrics is unknown. Further, comorbid bipolar disorder and adult ADHD are likely underrecognized with many patients only receiving treatment for one of these conditions. The occurrence of bipolar disorder with geriatric onset ADHD is unknown. Case presentation A 64-year-old Hispanic woman with a psychiatric history of bipolar I disorder (diagnosed in early adulthood) was diagnosed with ADHD suspected of geriatric onset, and able to be successfully managed on concurrent mood stabilizers and psychostimulant medication. Conclusions The findings of this case report emphasize the importance of appropriately recognizing and treating comorbid ADHD and bipolar disorder in any age group, including the geriatric population for which this occurrence appears to be very rare. Additionally, this case report demonstrates the safe utilization of psychostimulant medications in a geriatric patient with bipolar disorder without inducing a manic episode or other significant adverse reactions.